Environmental economics and natural resource management - David A. Anderson (London ; New York Routledge, Taylor & Francis Group, 2019)
The tools of environmental economics guide policymakers as they weigh development against nature, present against future, and certain benefits against uncertain consequences. The policies and research findings explained in this textbook are relevant to decisions made daily by individuals, firms, and governments.
Includes bibliographical references and index
Keywords: Environmental economics